Imagining the Possibilities: Investigating the Effects of a Possible Selves Intervention on Self-Regulatory Efficacy and Exercise Behaviour - Murru, Elisa (My University, 2008)
The present study was conducted to determine the effect of a possible selves intervention on self-regulatory efficacy and exercise behaviour. Participants were 19 men and 61 women (Mage= 21.43, SD = 3.28) who reported exercising less than 3 times per week. Participants were randomly assigned to a control condition, a hoped-for possible selves intervention condition, or a feared possible selves intervention condition. Participants in the hoped-for and feared possible selves conditions completed an activity where they imagined themselves in the future as either healthy, regular exercisers or unhealthy, inactive individuals, respectively. Participants in the control group completed a quiz about physical activity. Measures of self-regulatory efficacy (scheduling, planning, goal-setting, and barrier self-efficacy) were taken immediately before and after exposure to the intervention. Participants who received a possible selves intervention reported greater exercise behaviour 4 weeks post-intervention than participants in the control group (p = .05). Furthermore, planning self-efficacy was found to partially mediate the effect of the possible selves intervention on exercise behaviour. These findings suggest that possible selves may play a role in increasing exercise behaviour among inactive individuals. Future research is warranted to examine the role of possible selves interventions in increasing exercise behaviour and to determine which other variables may mediate this intervention-exercise behaviour relationship.
Keywords: Possible selves intervention, exercise behaviour, self-regulatory efficacy, inactive individuals